2018
DOI: 10.1017/aap.2018.3
|View full text |Cite|
|
Sign up to set email alerts
|

A Standard for the Scholarly Citation of Archaeological Data as an Incentive to Data Sharing

Abstract: How do archaeologists share their research data, if at all? We review what data are, according to current influential definitions, and previous work on the benefits, costs, and norms of data sharing in the sciences broadly. To understand data sharing in archaeology, we present the results of three pilot studies: requests for data by e-mail, review of data availability in published articles, and analysis of archaeological datasets deposited in repositories. We find that archaeologists are often willing to share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 70 publications
2
60
0
1
Order By: Relevance
“…Archaeobotanical data falls within the category of observational data in archaeology (Marwick & Pilaar Birch 2018). Archaeobotanical data is considered as the quantitative assessment of plant macrofossils present within a sample from a discrete archaeological context, which can include species identification, plant part, levels of identification (cf.…”
Section: Data Publication and Re-use Practices In Archaeobotany 21 mentioning
confidence: 99%
See 4 more Smart Citations
“…Archaeobotanical data falls within the category of observational data in archaeology (Marwick & Pilaar Birch 2018). Archaeobotanical data is considered as the quantitative assessment of plant macrofossils present within a sample from a discrete archaeological context, which can include species identification, plant part, levels of identification (cf.…”
Section: Data Publication and Re-use Practices In Archaeobotany 21 mentioning
confidence: 99%
“…ORA-Data), or social networking sites for academics (Academia.edu, ResearchGate). More widely in archaeology, some have observed that archaeological data is rarely published (Kintigh et al 2014), and recent reviews have reported low levels of data sharing (Huggett 2018;Marwick & Pilaar Birch 2018). A closely related issue is that of data reuse.…”
Section: Open Data Principles and Solutionsmentioning
confidence: 99%
See 3 more Smart Citations